(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
This work aims to evaluate the impact of ferrofluid containing dust particles and the presence of viscous dissipation on the boundary layer over a moving surface. The base fluids considered are kerosene and water, with ferroparticles of magnetite and cobalt ferrite. Ordinary differential equations (ODEs) were obtained by utilizing similarity transformations to change the governing equations of the boundary layer. The modified equations were subsequently solved numerically using the bvp4c solver integrated in MATLAB. The results of velocity profile, temperature profile, skin friction coefficient, including local Nusselt number were both presented in table and graphic formats. This study reveals that the ferrofluid phase as well as dust particle velocity decreases with decreases in the volume fraction of solid ferroparticles on a stretched surface. When the surface is shrinking, the velocities of both the ferrofluid and dust phases decrease with the reduction in the volume fraction of solid ferroparticles. The heat transfer rate in the kerosene-based fluid is higher when using the dusty cobalt ferrite ferrofluid compared to the water base fluid.